The effect of internet-based education to improve knowledge and practice toward COVID-19 prevention among community volunteer in rural area of West Java, Indonesia - Taryudi; Heri Firmansyah; Astri Mutiar; Heni Purnama (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2021)
Aims: This study aimed to determine the effect of internet-based education to improve knowledge and practice toward COVID-19 prevention among community volunteer in Indonesia. Design: This study is a quantitative study using the queasy-experimental two group pre-posttest design. Methods: The intervention in the form of internet-based education was offered to respondents in 5 sessions (45 minutes each meeting) in 3 weeks in the form of discussions utilizing power points and applications regarding COVID-19 prevention. the respondents are those who meet the inclusion criteria during the study: age over 18 years old, able to communicate well, not have visual and hearing impairment, can read and write, willing to be involved in research, and have access to android gadgets. Results: The number of samples in this study were 150 respondents consisting of 84 respondents (56.4) male and 66 respondents (44.0) female. Of these 150 respondents, 75 respondents were in the intervention group and 75 respondents were in the control group. COVID prevention knowledge before and after the internet-based education intervention increased significantly from 2.02 (SD=1.25) 2 to 3.45 (SD=1.31) with a t-value of 6.22 and a p-value of 0.000. In the scores of COVID-19 prevention practice, it was found that the intervention group data showed a significant Increased from 2.57 (SD = 0.98) to 3.13 (SD = 2.34) with a p-value of 0.000. Conclusions: This study found the significant improvement of knowledge and practice toward COVID-19 prevention using an internet-based education.